2016
DOI: 10.1007/s10620-016-4283-2
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Acute Endoscopic Retrograde Cholangiopancreatography in the Elderly

Abstract: ERCP can be safely and efficaciously performed on elderly patients. The high mortality should be taken into consideration when selecting therapeutic options.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 25 publications
2
22
0
5
Order By: Relevance
“…A recent retrospective study of 207 patients with acute cholangitis undergoing emergency ERCP found no significant differences in treatment success rates or AE among patients aged over or under 80 years . A retrospective study of 480 people aged >65 years reported an overall 30‐day mortality after ERCP of 10% . Therefore, careful consideration is required when deciding whether a therapeutic ERCP is truly indicated in a very old patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent retrospective study of 207 patients with acute cholangitis undergoing emergency ERCP found no significant differences in treatment success rates or AE among patients aged over or under 80 years . A retrospective study of 480 people aged >65 years reported an overall 30‐day mortality after ERCP of 10% . Therefore, careful consideration is required when deciding whether a therapeutic ERCP is truly indicated in a very old patient.…”
Section: Discussionmentioning
confidence: 99%
“…20 A retrospective study of 480 people aged >65 years reported an overall 30-day mortality after ERCP of 10%. 21 Therefore, careful consideration is required when deciding whether a therapeutic ERCP is truly indicated in a very old patient. Several reports on the safety of ERCP in older adults have been published.…”
Section: Discussionmentioning
confidence: 99%
“…Pancreatobiliary tract diseases, including choledocholithiasis, are commonly encountered in the elderly [13] and bile duct stone-related adverse events have significant morbidity in elderly patients because of the high prevalence of comorbidities such as chronic obstructive pulmonary disease, cardiovascular disorders and cerebrovascular accidents. In particular, the elderly are susceptible to procedure-associated infections, such as cholangitis or cholecystitis, due to the compromised innate and adaptive immune systems; this may largely explain the higher rates of morbidity and mortality in the elderly [14][15][16]. However, surgery in elderly patients carries higher complication and mortality rates when compared to the younger patient.…”
Section: Discussionmentioning
confidence: 99%
“…Endoscopic retrograde cholangiopancreatography (ERCP) is widely performed as the diagnostic and therapeutic tool intended for patients with pancreato-biliary diseases. The frequency of ERCP for elderly patients is increasing in accordance with the overall aging of the population worldwide (1). To date, ERCP has been known to be associated with severe adverse events, such as pancreatitis, gastrointestinal bleeding and perforation (1).…”
Section: Introductionmentioning
confidence: 99%
“…The frequency of ERCP for elderly patients is increasing in accordance with the overall aging of the population worldwide (1). To date, ERCP has been known to be associated with severe adverse events, such as pancreatitis, gastrointestinal bleeding and perforation (1). Although it has been reported that ERCP can be safely performed in elderly patients (2)(3)(4)(5)(6), the clinical status of these patients varies due to comorbidities, nutritional status, cognition, etc., which causes endoscopists to debate whether or not ERCP should be performed.…”
Section: Introductionmentioning
confidence: 99%